Marc Camille Chaimowicz, Roger Diener Armadillo House - Bechtler, Cristina; Bechtler, Cristina; Fischli, Fredi 1986-; Fischli, Fredi 1986-; Olsen, Niels 1989-; Olsen, Niels 1989- (Verlag der Buchhandlung Walther und Franz König, 2022)
The conversation between the artist Marc Camille Chaimowicz and the architect Roger Diener departs from their collaboration The Armadillo House in Basel. Rather than striving to build a "Meisterhaus" – an idealised representation of Diener & Diener’s architectural programme – they joined forces with someone who seems at first sight to be a most unlikely contributor to their project. The collaboration between artist and architect has led to a result that goes far beyond conventional parameters. Chaimowicz claims the interior as a pictorial space while also referencing the history of architecture, art and design. His agenda has been described as the celebration of domestic detritus and his spatial installations appear as painterly tableaus. From the 1970s onwards he advanced a critique of rigid, austere minimalism. For Diener, on the other hand, pictorial space is not a factor. Instead, he puts forward a modernist notion of non-expression, with architecture functioning as its raw material. In his architecture, it is not the insertion of culturally codified images but rather spatial configurations that shape the movement and circulation of inhabitants
Keywords: Chaimowicz, Marc Camille -- 1946-2024; Diener, Roger -- 1950-; (Produktform)Paperback / softback; Marc Camille Chaimowicz; Amadillo House; Roger Diener; Architektur; Bildende Kunst; Art and Architecture in Discussion; Dialog Kunst Architektur; (VLB-WN)1584: Hardcover, Softcover / Kunst/Architektur; Haus; Basel